Conceptual design methodologies appropriate to supersonic business jets - Sun, Yicheng (Cranfield University, 2018)
This project aims to study the status of the issues related to Supersonic Business Jet (SSBJ) conceptual design, to develop design methodologies appropriate to SSBJs, and to explore the design space of low-boom low-drag supersonic transport concepts. The design model appropriate to SSBJs is developed in the Cranfield multidisciplinary design analysis and optimization environment – GENUS. The mass breakdown, engine model, aerodynamic analysis, stability and control, and sonic boom prediction methods are developed in the GENUS framework. Optimizers help to explore the design space based on the model. Through the research, the current supersonic transport concepts are analysed and the supersonic natural laminar flow wing concept is found to leave little space for sonic boom mitigation. The most significant finding is the low-boom solution through the geometry shaping to the volume and lift effects. The low-drag requirement is not necessarily contradicted by the low-boom requirement. The low-boom optimization achieves a sonic boom reduction from 2.6 psf to 0.6 psf and the L/D increase from 8.96 to 10.67. The low-drag optimization achieves a L/D increase from 8.96 to 10.81 and sonic boom reduction from 2.6 psf to 1.0 psf. A low-boom low-drag SSBJ and a low-boom low-drag supersonic airliner concepts are designed in a multidisciplinary view. Pdf available on request and Howard Smith's permission.
Keywords: Aircraft conceptual design; multidisciplinary design optimization; supersonic business jet; supersonic airliner; sonic boom; low-boom low-drag